Sustaining the Balance: Exploring the Dynamic Interplay of Work-Life Conflict, Motivation, And Turnover Intention Among Saudi Female Employees in the Private Sector of Saudi Arabia - Al Zahrani, Manal Omar; Alshaikhmubarak, Abdulrahman (Journal of Posthumanism, 2025)
This paper examines the connection between work-life conflict, work motivation, and turnover intentions among female employees working in Saudi Arabia’s private sector sustaining the balance between work and life. Data for this study was collected from 120 women working in Saudi Arabia’s private sector. The findings suggest that even though work-life conflict is common among Saudi Arabian women working in the private sector, it has a low negative impact on their motivation at work. The study also established that work-life conflict among women employed in Saudi Arabia’s private sector had no direct impact on the women’s intent to resign from their jobs. However, the women’s work motivation mediated the link between work-life conflict and turn-over intentions, even though the ‘mediated linkage’ was also very weak. Organizations should implement practices that minimize the conflict between work and life to attain a sustainable balance within the workforce. This study’s originality stems from extensive research on the dy-namics surrounding female employment in Saudi Arabia’s job market. Its value also arises from the development of a conceptual framework that explains work motivation and turnover inten-tions through the lens of four human motivation theories. Subsequently, its results provide stakeholders of Saudi’s labor sector with empirical data on the influence that work-life conflict has on female employees’ job motivation and turnover intentions.